Correlation between group behavior and quorum sensing in Pseudomonas aeruginosa isolated from patients with hospitalacquired pneumonia - Li, Yong; Qu, Hong-Ping; Liu, Jia-Lin; Wan, Huan-Ying (Journal of Thoracic Disease, 2014)
Background: This study investigated the correlation between the expression of the Las and Rhl quorumsensing (QS) systems and the communal behavior (motility, biofilm formation, and pyocyanin production) of Pseudomonas aeruginosa (P. aeruginosa) isolated from patients with hospital-acquired pneumonia. Methods: We analyzed 138 P. aeruginosa isolates from 48 patients (30 men and 18 women; age 68.18±15.08 years). P. aeruginosa clinical isolates were assessed for Las and Rhl gene expression and bacterial motility, biofilm formation, and pyocyanin production. Results: P. aeruginosa swimming, twitching, and swarming motility positively correlated with the expression of LasI, LasR, and RhlI (P0.05). At all analyzed time points, a significant positive correlation was found between biofilm formation and the expression of LasI, LasR (P